HYGIENIC ASPECTS OF ATMOSPHERIC AIR ENVIRONMENT - O‘ngboyeva Dilorom O‘rozovna; Parmankulova Nargiza Xatamkulovna (Web of Journals Publishing, 2024)
In this article, atmospheric layers, factors that characterize the physical properties of the atmosphere include air temperature, humidity and movement, atmospheric pressure, solar radiation entering the atmosphere, atmospheric air and the composition of air when a person exhales, breathing when the oxygen supply of the human body is disturbed, the central nervous system, about serious changes in the cardiovascular system and other systems, indicators of meteorological factors, partial pressure, causes of "mountain sickness", atmospheric pressure, carbon (IV)-oxide, hygienic importance of air held.